Bibliometric Analysis Of Research Trends On Air Pollution And Its Impact On Brain Health, 2013–2023 - As, Zufikar Ali; Suhartono, Eko; Pahruddin, Muhammad (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2025)
This study analyzes global trends related to the impact of air pollution on brain health using the bibliometric method. Data was collected from the Scopus database with the keyword